Analysis of Heavy Metals Concentration and Pollution Index on Water Quality in Labuan Beach Fishery Port Area, Banten - Roza Ruspita (JURNAL SAINS NATURAL, 2023)
Labuan Coastal Fishing Port (PPP) is an area with great potential for development in the economic and tourism sectors. Apart from being the center of the fishing industry in Pandeglang Regency, PPP Labuan also has beach tourist attractions. Some activities could cause the entry of heavy metals into waters and affect water quality. These activities include ships refuelling, ships exhaust emissions, ships washing and paint spills, as well as beach tourism activities. The pollution index is used to determine the level of pollution in waters. This research aimed to analyze water quality and pollution indices based on the heavy metals content iron (Fe), nickel (Ni), and copper (Cu). Samples were taken from three observation stations, namely the beach tourist area (station 1), the fish auction site (station 2), and the pier (station 3). Analysis of the heavy metals Fe, Ni, Cu was carried out using the Atomic Absorption Spectrophotometer method and the results were compared with Indonesian government reulation, PP No. 82/2001. Pollution index analysis wasusing the pollution index method. The heavy metals content of iron (Fe) ranged from 1.761 – 6.907 mg/L, nickel (Ni) ranged from 0.079 – 0.269 mg/L, and copper (Cu) is < 0.001 mg/L. Based on the pollution index (IP), station 1 was lightly polluted with an IP value of 3.75. At station 2 it was moderately polluted with an IP value of 5.91, and at station 3 it was lightly polluted with a value of 4.2.